A novel arterial Wick for gas–liquid phase separation. Issue 4 (17th January 2019) - Beheshti Pour, Negar; Thiessen, David B.
Abstract : Gas–liquid phase separation under microgravity conditions or in small‐scale fluidic systems represents a challenge for two‐phase liquid‐continuous systems. In this study, capillary channels formed by 3‐mm diameter stretched stainless‐steel springs coated with a commercial superhydrophobic coating are used to remove air bubbles from water. A single channel is capable of absorbing a stream of 3.7‐mm diameter bubbles impinging on a small area of the channel at a rate of over 50 bubbles/s. High‐permeability walls lead to fast individual absorption events (4 ms for 2.5‐mm bubbles) where bubble collapse time is limited by the inertia of the surrounding liquid. A horizontal three‐channel array has been shown capable of absorbing impinging bubbles from a sparger at superficial gas velocities of 0.03 m/s. The ultimate capacity of the 3‐mm diameter channel is predicted to be much higher than what could be measured with the existing apparatus. © 2018 American Institute of Chemical Engineers AIChE J, 65: 1340–1354, 2019